Enhancing Approach for Information Security in Hadoop: Retracted - Awasthi, Yogesh; Sharma, Ashish (JITCE (Journal of Information Technology and Computer Engineering), 2020)
This article by Yogesh Awasthi (Email: dryogeshawasthi@lfu.edu.krd) has been retracted (i.e. withdrawn from the press) for violating our Publication Ethics.